Application of Radioactive Tracers in Upgradation of Industrial Grade Ion Exchange Resin (Amberlite IRA-400) - Lokhande, R.S.; Singare, P.U. (Asian Journal of Chemistry, 2010)
The exchange rates of ion exchange resin are determined byapplication of 131I as a tracer isotope. The exchange study carriedout in this investigation deals with understanding the effectivenessof ion exchange resin (in iodide form) Amberlite lRA-400 at differentconcentrations of potassium iodide solution (electrolyte)-withtemperature of solution varying from 27-48°C by keeping amountof ion exchange resin constant (1.0 g). The exchange study is alsocarried out by varying amount of ion exchange resins, for fixedtemperature (27.0oC) and for fixed concentration of potassiumiodide solution (0.005 M).